Investigating Features Related to Chinese Linguistic Complexities among International Students Learning Chinese as a Foreign Language - Mohammad Nasim Tahsildar (International Journal of Theory and Application in Elementary and Secondary School Education, 2019)
This paper reports on a study investigating features related to Chinese linguistic complexities for international students enrolled in Chinese courses in China. The main objective of this study is to highlight the major feature of Chinese complexities encountered by international students and explore whether international students’ native languages interfere with the process of learning Chinese. The study used a survey questionnaire developed by Zhang (2013) to collect the data from 147 male and female Bachelor, Master and Ph.D. students enrolled in basic Chinese classes in two universities in China. Based on certain Descriptive and ANOVA calculations, findings of the study indicate that the participants indeed experienced different features related to linguistic complexities. Moreover, the results also revealed the participants’ native language interference in the process of learning Chinese.